Design of Planar Dielectric Resonator Antenna Array at 28 GHz - Nuramirah Mohd Nor; Mohd Haizal Jamaluddin; Muhammad Ramlee Kamarudin; Siti Zareen Naqiyah Zool Ambia (Institute of Advanced Engineering and Science, 2017)
This article presents a planar array of rectangular Dielectric Resonator Antenna operating for 28 GHz applications. The proposed antenna is formed through two stages of designs which are a single element and planar array. It is made up from a ceramic material with a dielectric constant of 10 and mounted on RT/Duroid 5880 with a relative permittivity of 2.2 and a thickness of 0.254 mm. A prospective study using three different configurations of three by three planar array is done in order to obtain the best performance in terms of bandwidth, gain, and cost reduction. Besides that, this study is also conducted for a beam steering capability of each configuration. Finally, the best configuration is proposed for 5G application.